Оцінка можливості використання повідсікового моделювання процесів в проточній частині парової турбіни в задачах одночасної оптимізації теплових схем та турбін - Шерфедінов, Різа Бахтіярович; Усатий, Олександр Павлович (Національний технічний університет "Харківський політехнічний інститут", 2023)
Розглянуто два варіанти постановок задачі розрахунку проточної частини (ПЧ)парової турбіни з використанням удосконаленого одновимірного повідсікового моделювання термо- та газодинамічних процесів в ПЧ при заданих величинах параметрів пари на вході і виході із циліндру та між його відсіками. Перший варіант постановки забезпечував визначення масової витрати пари на вході в кожен відсік при заданій геометрії ПЧ. Другий варіант постановки дозволяв провести послідовний розрахунок кожного відсіку при заданих величинах масової витрати пари в голову кожного відсіку, а також параметрів пари між відсіками за рахунок відповідного коригування значень ефективних кутів виходу соплових решіток усіх ступенів кожного відсіку. В якості об'єкту дослідження було вибрано циліндр середнього тиску (ЦСТ) турбіни К-540-23,5. Розрахункові дослідження були сплановані, проведені і обробленні з використанням методів теорії планування експерименту. Виконані порівняння результатів розрахунків з використанням обох варіантів повідсікового моделювання термо- та газодинамічних процесів між собою та результатами отриманими з використанням загальноприйнятого варіанту поступеневого моделювання роботи ПЧ парової турбіни. Порівняння показали, що для розв’язання задач оптимального проєктування доречніше використовувати другий варіант постановки удосконаленого одновимірного повідсікового моделювання термо- та газодинамічних процесів в ПЧ.

Consideration is given to the two options of the problem formulation to calculate the flow part (FP) of a steam turbine using an improved one-dimensional compartment-by-compartment modeling of thermal and gas-dynamic processes in the FP at given values of steam parameters at the inlet and outlet of the cylinder and between its compartments. The first option of the problem formulation enabled the determination of the mass flow rate of steam at the inlet to each compartment for a given flow part geometry. The second option of the problem formulation enabled a sequential calculation of each compartment at given values of the mass flow rate of steam to the head of each compartment, as well as steam parameters between the compartments due to an appropriate adjustment of the values of the effective exit angles of the nozzle arrays of all the stages of each compartment. The medium pressure cylinder (MPC) of the K-540-23.5 turbine was chosen as the object of investigation. Computational studies were planned, carried out and the data were processed using the methods of the experimental design theory. The obtained calculation data were compared with each other and with the data obtained using the generally accepted version of stepwise modeling of the operation of the FP of the steam turbine, using both options of the compartment-by-compartment modeling of thermal and gas-dynamic processes. The use of the first option for modeling the processes in the flow part results in a considerable change in the mass flow of steam taken for heating the feed water, which has a negative impact on the operation efficiency of the thermal circuit. In this case, the processes may develop in a way when it is necessary not to take steam to heat the feed water, but to additionally blow it into the flow part, which does not correspond to the parameters of the thermal circuit and cannot be implemented. The second option of the compartment -by-compartment modeling ensures the determination of the values of the mass flow rates of steam for each compartment that are close to the values obtained by the stepwise calculation of the flow part. The comparison of the two options showed that it is better to use the second option of the formulation of an improved one-dimensional compartment-by-compartment modeling of thermal and gas-dynamic processes in the flow part for optimal design problems.
Assessing the possibility of using the compartment-by-compartment modeling of processes in the flow part of a steam turbine for problems of the optimal design of axial turbines
Keywords: парова турбіна; проточна частина; відсік; математичне моделювання; оптимальне проєктування; планування експерименту; steam turbine; flow part; compartment; mathematical modeling; optimal design; experimental planning